Expanding severe acute respiratory infection (SARI) surveillance beyond influenza: The process and data from 1 year of implementation in Vietnam. Issue 5 (10th June 2018) - Alroy, Karen A.; Do, Trang Thuy; Tran, Phu Dac; Dang, Tan Quang; Vu, Long Ngoc; Le, Nga Thi Hang; Dang, Anh Duc; Ngu, Nghia Duy; Ngo, Tu Huy; Hoang, Phuong Vu Mai; Phan, Lan Trong; Nguyen, Thuong Vu; et al.
Abstract : Background: In 2016, as a component of the Global Health Security Agenda, the Vietnam Ministry of Health expanded its existing influenza sentinel surveillance for severe acute respiratory infections (SARI) to include testing for 7 additional viral respiratory pathogens. This article describes the steps taken to implement expanded SARI surveillance in Vietnam and reports data from 1 year of expanded surveillance. Methods: The process of expanding the suite of pathogens for routine testing by real‐time reverse transcriptase–polymerase chain reaction (rRT‐PCR) included laboratory trainings, procurement/distribution of reagents, and strengthening and aligning SARI surveillance epidemiology practices at sentinel sites and regional institutes (RI). Results: Surveillance data showed that of 4003 specimens tested by the RI laboratories, 20.2% (n = 810) were positive for influenza virus. Of the 3193 influenza‐negative specimens, 41.8% (n = 1337) were positive for at least 1 non‐influenza respiratory virus, of which 16.2% (n = 518), 13.4% (n = 428), and 9.6% (n = 308) tested positive for respiratory syncytial virus, rhinovirus, and adenovirus, respectively. Conclusions: The Government of Vietnam has demonstrated that expanding respiratory viral surveillance by strengthening and building upon an influenza platform is feasible, efficient, and practical.